2021
DOI: 10.1002/pssa.202000751
|View full text |Cite|
|
Sign up to set email alerts
|

A Review on the Recent Progress of Silicon‐on‐Insulator‐Based Photodetectors

Abstract: The family of photodetectors plays an important role in multiple applications. Extensive research and continuous development of photodetectors has enriched their functionalities and improved their performances. The silicon-on-insulator (SOI) technology extends the concepts and merits of photodetectors. Herein, the recent progress of the SOI-based photodetectors is reviewed from the viewpoint of operation principles and performances. Silicon and Germanium photodiodes with conventional PIN structure are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…If is larger than the depleted region (about 0.5 µm for the slightly P-type doped “intrinsic” region of the reported PIN diodes), then diffusion of charge carriers in the quasi-neutral or depleted by the vertical field region must be considered. With back gate bias, the surfaces in the region of the SOI device layer have “field-induced doping” [ 15 ]. For negative , induced P-type doping is connected to the P+ electrode of the PIN diode.…”
Section: Resultsmentioning
confidence: 99%
“…If is larger than the depleted region (about 0.5 µm for the slightly P-type doped “intrinsic” region of the reported PIN diodes), then diffusion of charge carriers in the quasi-neutral or depleted by the vertical field region must be considered. With back gate bias, the surfaces in the region of the SOI device layer have “field-induced doping” [ 15 ]. For negative , induced P-type doping is connected to the P+ electrode of the PIN diode.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for the silicon-on-insulator platform, germanium photodetectors can be epitaxially grown on the same chip. 19 The silicon nitride platform may need heterogenous integration of the high-speed modulator because of the absence of high-speed electro-optic modulators based on the silicon nitride. 20 And full integration of the optical components can be achieved on the indium phosphide-based platform.…”
Section: The Beamsteering Device Simulation Modelmentioning
confidence: 99%
“…Recently, the photodetector application of CsPbB 3 single crystal has been a point of interest and it shows promising results in replacing the conventional inorganic photodetectors. [54][55][56] Ding et al 57 reported the CsPbBr3 single crystal prepared by the antisolvent method, and their steady and transient performances delivered highest responsivity of 0.028 A/W. Zhang et al 58 prepared large-size CsPbBr3 single crystal by using the vertical Bridgman method with low trap density by using a modified Bridgman method.…”
Section: Introductionmentioning
confidence: 99%